Pengaruh Konsumsi Air Putih terhadap Gambaran Kalsium Oksalat dalam Urin Mahasiswa Akademi Analis Kesehatan Pekalongan Tahun 2021 - Fitrianingsih Fitrianingsih; Abdul Ghofur; Dwi Ardinianti (Jurnal Kebidanan Harapan Ibu Pekalongan, 2022)
Calcium oxalate includes urinary sediment as a combination of calcium and oxalate, calcium can be deposited by oxalate forming calcium oxalate that the body cannot absorb, then into insoluble salt deposits and become kidney stone disease. Water prevents the formation of calcium oxalate crystals. So it is recommended to consume at least 2 liters a day so that the urine released will increase and reduce the concentration of salt and minerals in the body. This study to find out the effect of water consumption on the picture of oxalate crystals in the urine of AAK Pekalongan students before and after consuming water as much as 2 liters per day. Types of analytical observational studies with different T paired test statistical tests, sample numbers of 22 samples and microscopic examination. The results of the study of calcium oxalate in urine before consuming water as much as 2 liters obtained the results of 6 samples (27.28%) negative, 5 samples (22.72%) positive 1.1 sample (4.55%) positive 2 and 10 samples (45.45%) positive 3, while in the sample after consuming water as much as 2 liters obtained 20 samples (90.90%) negative, 1 sample (4.55%) positive 1.1 samples (4.55%) positive 2 and 0 samples (0%) positive 3. Statistical results state that there is an influence before and after water consumption on the picture of calcium oxalate in the urine of AAK Pekalongan students.